2008
DOI: 10.1002/bjs.6054
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes following total minimally invasive oesophagectomy

Abstract: Background: Minimally invasive oesophagectomy (MIO; thoracoscopy, laparoscopy, cervical anastomosis) is a complex procedure and few substantial series have been published. This study documented the morbidity, mortality and challenges of adopting MIO in a specialist unit in the UK. Conclusion: MIO can be performed with acceptable mortality and morbidity rates in an unselected series of patients. There was more morbidity related to gastric tube ischaemia than was expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 44 publications
6
60
0
Order By: Relevance
“…One potential benefit of laparoscopic surgery shown by this study was the decrease in initial transfusion requirements for a significant proportion of patients as well as a significant decrease in the median length of postoperative ventilation. Similar results have been reported with minimally invasive esophagectomy for 77 patients, who had a median intraoperative blood loss of 425 ml and a median blood transfusion requirement during the hospital stay of 0 units (range, 0-8 units) [14]. Although postoperative ventilation time was not reported in this study, the median intensive care unit (ICU) length of stay was 6.5 days [14].…”
Section: Discussionsupporting
confidence: 86%
“…One potential benefit of laparoscopic surgery shown by this study was the decrease in initial transfusion requirements for a significant proportion of patients as well as a significant decrease in the median length of postoperative ventilation. Similar results have been reported with minimally invasive esophagectomy for 77 patients, who had a median intraoperative blood loss of 425 ml and a median blood transfusion requirement during the hospital stay of 0 units (range, 0-8 units) [14]. Although postoperative ventilation time was not reported in this study, the median intensive care unit (ICU) length of stay was 6.5 days [14].…”
Section: Discussionsupporting
confidence: 86%
“…1 In a case series by Berrisford et al, the authors reported on 70 MIOs, with 9 patients (12.9%) suffering gastric conduit complications. 17 Several authors have tried to solve the problem of gastric tube ischaemia after laparoscopic oesophagectomy. In an experimental study in pigs, significant improvement in gastric tube blood flow was found following intravenous administration of unmodified prostaglandin E 1 (PGE1) and lipo-PGE1 (p<0.01).…”
mentioning
confidence: 99%
“…18 In addition, it seems clear that MIO is associated with complications very rarely seen in open oesophagectomy, including gastric conduit necrosis. 19 Guidelines published by the National Institute for Health and Clinical Excellence and by professional associations in the UK concluded that there was no convincing evidence that MIO was superior to open oesophagectomy.…”
Section: Surgical Approachmentioning
confidence: 99%